APLIKASI BOKASHI KULIT NENAS DAN PUPUK NPK ORGANIK UNTUK PENINGKATAN.PERTUMBUHAN.DAN HASIL TANAMAN.TERUNG.UNGU (Solanum melongena L.) - Ahmad Ruliansyah; Ernita; Sri Mulyani (DINAMIKA PERTANIAN, 2022)
The aim of the work was to find out the interaction between pineapple peel bokashi and organic NPK fertilizer and the main effect in increasing the growth and yield of purple eggplant (Solanum melongena L.). The study was conducted at the experimental farm of the Faculty of Agriculture of the Riau Islamic University from February to May 2020. This experimental design was 4 x 4 factorial using a completely randomized design with 3 replications. The first factor was the dose of pineapple peel bokashi consists of 4 levels: 0, 0.75, 1.5, 2.25 kg per plot. The second factor was the dose of NPK organic Fertilizer, consisting of 4 level: 0, 7.5, 15.0, 22, 5 gram per plant. The parameters observed were plant height, flowering age, harvest age, number of fruit crops, weight of fruit per plant, weight of fruit per fruit, number of residual fruits. The data were analyzed statistically and continued with the real difference test (BNJ) at the 5% level. The results showed that the interaction of pineapple peel bokashi and organic NPK had a significant effect to all observation parameters and the best treatment was a combination of pineapple skin bokashi 2.25 kg/plot and NPK organic 22.5 g/plant. The main effect of pineapple peel bokashi dose was significant on all observed parameters with the best treatment was 2.25 kg / plot. The main effect of organic NPK was significant for all parameters. The best treatment was found on organic NPK dose of 22.5 g/plant.